Studi Kasus: Penerapan Pursed Lip Breathing terhadap Ketidakefektifan Bersihan Jalan Napas pada Pasien Penyakit Paru Obstruktif Kronis (PPOK) - Tio Anggara; Erida Fadila; Dwiyanti Purbasari (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a chronic condition with high morbidity and mortality rates, characterized by persistent airflow obstruction leading to ineffective airway clearance, dyspnea, and decreased oxygen saturation. Pursed Lip Breathing (PLB) is a non-pharmacological therapy that is easy to apply and has been proven effective in reducing dyspnea and improving respiratory function in COPD patients.Objective: To explore the effectiveness of applying the Pursed Lip Breathing technique on ineffective airway clearance in COPD. Method: The study used a descriptive case study design on two COPD patients with GOLD stages 2–4. The PLB intervention was given twice daily (morning and afternoon) for three consecutive days, each session lasting 5–10 minutes with a procedure of 2 seconds of inspiration through the nose and 4–6 seconds of expiration through pursed lips. Respiratory rate (RR) and oxygen saturation (SpO₂) were measured before and after the intervention using a pulse oximeter. Results: The average respiratory rate decreased from 28 breaths/minute to 23 breaths/minute, and the average oxygen saturation increased from 92% to 96% after the three-day PLB intervention. All patients reported a subjective reduction in shortness of breath and an improved ability to perform light activities, with no recorded side effects.